Odpowiedzi

Najlepsza Odpowiedź!
2010-02-19T22:05:38+01:00
A)
2a(x + 5y) + 3x (a - 5y) = 2ax+10ay+3ax-15xy=5ax+10ay-15xy
b)
-4b(2a - 8y) + 3y (b - 7a) =-8ab+32by+3by-21ay= -8ab+35by-21ay
c)
(-0,4y - 4)5x² - 2y(x² - 6) = -2x²y -20x² - 2x²y+12= -4x²y -20x² +12
d)
7b(5 + 3ax) - (2a - 5b)2bx = 35b+21axb -4axb+10b²x=35b+17axb+10b²x

3 3 3
2010-02-19T22:07:07+01:00
A) 2a(x + 5y) + 3x (a - 5y) = 2ax+10ay + 3ax-15xy = 5ax+10ay-15xy

b) -4b(2a - 8y) + 3y (b - 7a) = -8ab+32by+3by-21ay = -8ab+35by-21ay

c) (-0,4y - 4)5x² - 2y(x² - 6) = -2x²y-20x²-2x²y+12y = -20x²-4x²y+12y

d) 7b(5 + 3ax) - (2a - 5b)2bx = 35b+21abx-4abx+10b²x = 35b+17abx+10b²x
3 4 3
2010-02-19T22:10:45+01:00
A) 2ax+10ay+3xa-15xy=5ax+10ay-15xy
b) -8a+32y+3yb-21ya
c)2yx²-20x²-2yx²+12y=-20x²+12y
d)7b(5 + 3ax) - (2a - 5b)2bx = 35b+21bax-4bxa+10b²x= 35b+17bxa+10b²x

chyba tak.. nie pamiętam dobrze.. ;) dawno temu takie coś robiłam. ;]
1 4 1